VIOLÊNCIA E CRIMINALIDADE IMIGRANTE EM PROCESSOS CRIMINAIS – MALLET/PR (1913-1940) - FERRANDO, LOIANA MAIARA ZVIEGICOSKI (2022)
The present study aims to analyze violence and crime involving immigrants in Mallet-PR. We took as a source the police investigations and criminal cases that are located at the Documentation and Memory Center (CEDOC/I) of Unicentro, Irati-PR campus and at the Mallet District Courthouse. The temporal beacons were the year 1913, the first judicial record, after the political emancipation of the municipality, until the year 1940, when a new Brazilian Penal Code was instituted. The Malletense territory became the stage for population displacements, especially of Europeans, attracted by the immigration policy, who began to live with the other settled groups. In this context, immigrants established different practices and behaviors, some criminalized and violent, which did not match those idealized by oligarchic groups and governors of Paraná. Through the selected documentation, in a qualitative and quantitative way, we investigated such records, therefore, the profile of those involved, the spatialities and temporalities of the criminalized actions, the defense and prosecution strategies, the interethnic and intraethnic relationships, the protection and assistance, the issue of work, among other elements that make up immigrant crime. In this way, these sources are loaded with information that allow us to rethink the knowledge already built and the regions marked by immigration.